ASSESSMENT OF FIXED DENTURES QUALITY - I.V. Yanishen (Ukrainian Medical Stomatological Academy, 2016)
Abstract. The purpose of the research was aimed at comparative analysis of quality of fixed dentures at the stages of its clinical durability. Materials and Methods. The results of expert evaluation, performed in compliance with f.043/о in 10 medioprophilactic institutions comprised the following mode of dataware: the total amount of studied fixed dentures was 35950 pieces; the total number of prosthodontist was 75 individuals, dental mechanics were 103 individuals. The comparative quality assessment of 20329 artificial crowns (13304 plastic crowns and 7025 combined crowns according to Byelkin, Borodyuk, Ahmetov), 15621 bridge dentures (9789 plastic dentures and 5832 combined dentures) has been made at the stages of clinical durability of prosthetic appliances. In comparative quality assessment of fixed dentures the following indicators have been used: index of clinical- technological quality (ІТЯ - total number of signs of decrease in quality of prosthetic appliance and total number of such appliances ratio) and efficiency index (ЯП, % - density of prosthetic appliances of satisfactory quality). Results and Discussion. Time periods and signs of decrease in quality of plastic and combined artificial crowns have been studied. The study showed that quality of artificial crowns is defined by the length of dentures' clinical durability and their type (plastic/combined). So, at the early stage of clinical durability artificial crowns are characterized by the higher level of quality, than combined ones (ЯП: (96,8±0,8)% and (92,1±1,6)%, respectively; р<0,05), which depends on overall rate of specific signs of decrease in quality of the appliances ((3,2±0,8)% for plastic crowns; (12,0±2,5)% for combined crowns; р<0,01) and ratio of prosthetic appliances with the signs of quality decrease (ІТЯ : (1,4±0,1)% for plastic crowns; (1,3±0,1)% for combined crowns; р<0,01). In the remote period of clinical durability plastic crowns are characterized by more apparent decrease in quality level of prosthetic appliance than combined ones (ЯП: (52,9±3,5)% and (39,1±3,7)%, respectively; р<0,05), which occurs, first of all, due to increase of the overall rate of individual signs of decrease in quality of appliance ((47,1±3,5)% for plastic crowns; (77,9±9,6)% for combined crowns; р<0,01); at the same time ІТЯ remains stable. The quality of bridge dentures depends on different reasons and is also defined by the length of clinical durability of the appliance and its type (plastic or combined ones). The decrease in quality of bridge dentures occurs due to the increase of overall rate of specific signs of decrease in quality of the appliance ((69,1±4,6)% for plastic dentures; (65,2±5,0)% for combined ones; р<0,05); at the same time ІТЯ of comparing appliances does not significantly differ and constitutes on the average 1,4+0,07. Conclusions. The technique of comparative analysis of quality of fixed dentures has been studied and implemented at the stages of clinical durability of plastic and combined artificial crowns and bridge dentures according to the range of indices.  It has been proved by evidence, that quality of artificial crowns is defined by the length of clinical durability of the appliance and is significantly higher, than the quality of combined ones at the early stage of their clinical durability; at the same time in the remote period of clinical durability plastic crowns are characterized by higher rates of quality index. It has been proved by evidence that quality of bridge dentures is defined by the length of clinical durability of the appliance, their type, and does not depend on similarity of the constructive material in the early and remote period. Perspectives of further research, devoted to this problem, are connected with grounding of constructive-and- compliant constructive and supplemental dental materials as well as study of quality of life of patients at the stages of clinical durability of fixed dentures.